Herbicide programs for seasonal windmillgrass control - Mitchell, Nicholas James (Kansas State University, 2020)
Windmillgrass (Chloris verticillata Nutt.) is a problematic perennial grass weed commonly found in the Midwest of the United States. Currently, there are only two labeled chemical control options in turfgrass. Tenacity® (mesotrione) is labeled for two applications for control while Pylex™ (topramezone) is labeled for a single application for control. However, other herbicides could potentially provide adequate control. Also, there is no literature reported for application timing for optimal windmillgrass control. Therefore, research was conducted to determine if a single application of a common selective perennial grass herbicide would completely control windmillgrass, and to evaluate the herbicide efficacy when applied at spring, summer, or fall application timings. Single herbicide application never achieved complete control of windmillgrass; it was also determined that no differences in control was observed regardless of application timing. Previous research reported herbicide combinations as well as sequential applications could provide better control than herbicides applied alone or as a single application. Therefore, additional research trials were conducted to explore the efficacy with the addition of triclopyr to mesotrione, topramezone, and fenoxaprop as well as triclopyr alone. Sequential applications of these herbicides and herbicide combinations were also applied. It was determined that the addition of triclopyr to these herbicides provided significantly better control of windmillgrass with both single and sequential applications compared to these herbicides alone. Also, two applications of mesotrione and topramezone applied in the early fall alone provided complete control of windmillgrass by spring green up. Additional research was conducted to determine the effects of windmillgrass response to glyphosate at different rates with fall application. It was recorded at spring green up all glyphosate rates at or above 1.66 kg ae ha⁻¹ provided complete control of windmillgrass.
Keywords: Windmillgrass; Weed control; Herbicide efficacy